The cyclopropylcarbinyl route to γ-silyl carbocations - Creary, Xavier (Beilstein Journal of Organic Chemistry, 2019)
The mesylate derivative of cis-1-hydroxymethyl-2-trimethylsilylcyclopropane has been prepared, along with a number of related mesylates and triflates with substituents on the 1-position. These substrates all solvolyze in CD3CO2D to give products derived from cyclopropylcarbinyl cations that undergo further rearrangement to give 3-trimethylsilylcyclobutyl cations. These 3-trimethylsilylcyclobutyl cations are stabilized by a long-range rear lobe interaction with the γ-trimethylsilyl group. When the substituent is electron-withdrawing (CF3, CN, or CO2CH3), significant amounts of bicyclobutane products are formed. The bicyclobutanes are a result of γ-trimethylsilyl elimination from the cationic intermediate that has an unusually long calculated Si–C bond. The solvolysis chemistry of mesylate and triflate derivatives of trans-1-hydroxymethyl-2-trimethylsilylcyclopropane and 1-substituted analogs can be quite different since these substrates do not generally lead to 3-trimethylsilylcyclobutyl cations.
Keywords: bicyclobutane; carbocation; cyclopropylcarbinyl; rearrangement; silicon